Identifikasi Potensi Dodol Buah Lontar Sebagai Daya Tarik Wisata Kuliner di Desa Baraya, Kabupaten Jeneponto - Rafika Hayati; Miranda (Politeknik Bosowa, 2026)
Palm fruit (Borassus flabellifer) is a local food resource abundantly found in Jeneponto Regency; however, its utilization remains limited and underdeveloped within the tourism sector. This study aims to identify the potential of palm fruit dodol as a culinary tourism attraction in Baraya Village, Jeneponto Regency, and to analyze its development prospects using the 4A tourism framework (attraction, accessibility, amenities, and ancillary services). A qualitative approach was employed through library research supported by participatory observation and semi-structured interviews with purposively selected key informants, including village officials, community leaders, and representatives of women’s household groups. The findings indicate that palm fruit dodol production has strong potential as a culinary tourism attraction by integrating local food resources, traditional processing methods, and local cultural values. The dodol-making process can be developed into a participatory tourism experience that enhances the economic value of palm fruit and supports income diversification for local communities. Nevertheless, the development of culinary tourism in Baraya Village faces challenges related to accessibility and tourism amenities. This study concludes that palm fruit dodol has the potential to become a flagship local culinary tourism product in Jeneponto Regency, provided that integrated management and institutional support are strengthened